On geologic timescales, plant carbon isotope fractionation responds to precipitation similarly to modern plants and has a small negative correlation with pCO2. (1st February 2020) - Schlanser, Kristen; Diefendorf, Aaron F.; Greenwood, David R.; Mueller, Kevin E.; West, Christopher K.; Lowe, Alexander J.; Basinger, James F.; Currano, Ellen D.; Flynn, Andrew G.; Fricke, Henry C.; Geng, Jie; Meyer, Herbert W.; et al.
Abstract: Leaf carbon isotope fractionation (Δleaf ) is sensitive to environmental conditions and can provide insights into the state and evolution of leaf gas-exchange in response to climate and environment factors. In modern plants, water availability is the strongest environmental predictor of Δleaf across sites that experience relatively uniform and low concentrations of CO2 in the atmosphere ( p CO2 ). Growth chamber experiments show Δleaf of modern plants can also be sensitive to changing p CO2 . However, over geologic time, it is uncertain how Δleaf has responded to shifts in p CO2 and precipitation. To address this problem, we collected sediment (rock) samples from fossil leaf sites that represent a range of p CO2 values from ∼200 to 900 ppmV, over 40 degrees of latitude from New Mexico to the High Arctic, and 40 million years spanning the Late Cretaceous to the Oligocene. For each site, the carbon isotope composition of atmospheric CO2 (δ 13 Catm ), p CO2, mean annual precipitation, and mean annual temperature were constrained from independent proxies. From sediment samples, we extracted long-chain n -alkanes (biomarkers derived from plant wax). We then measured the carbon isotope ratios of sediment-derived n -C29 and n -C31 alkanes to calculate Δleaf . Results show a negative correlation between Δleaf and p CO2 even after controlling for mean annual precipitation. The Δleaf response to p CO2 is small (−0.3 ± 0.09‰/100 ppmV), suggesting plants are adjusting internal leaf CO2 concentrations to atmospheric p CO2 concentrations, likely by optimizing leaf gas-exchange to maximize carbon intake and minimize water loss in response to environmental conditions. Similar to previous studies of geologic sediments and living plants, Δleaf was also positively correlated with water availability and, to a lesser extent, sensitive to plant type and possibly altitude. As a result, the Δleaf – p CO2 relationship in the geologic past may be more complex than observed in modern studies and therefore, precludes its use as a p CO2 proxy.